2006
DOI: 10.1248/bpb.29.141
|View full text |Cite
|
Sign up to set email alerts
|

Serum Aminotransferase Activity as a Predictor for Estimation of Total Clearance of Hepatically Metabolized Drugs in Rats with Acute Hepatic Failure

Abstract: In treating patients with hepatic failure, it is necessary to set an appropriate drug dosing schedule to take into account of their altered drug disposition kinetics. However, little work has been done to estimate the decrease of total clearance (CL tot ) in relation to the degree of residual hepatic function. Therefore, there is great need for a suitable marker to quantitatively predict the hepatic metabolic capacity in patients with hepatic failure.In humans, there are five predominant families of cytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Moreover, it is important to note that despite that SCN-DOX resulted in a high accumulation of DOX in the liver, better liver function than that in the animals received free DOX was observed at the end of the study, as demonstrated by a significant reduction of serum AST in mice treated with SCN-DOX (Figure 8). Of note, DOX is excreted predominantly through the hepatobiliary route [54] and there is a good negative correlation between serum AST activity and hepatic intrinsic clearance [55]. Therefore, it is tempting to speculate that SCN-DOX accumulated in the liver was not significantly taken up the hepatocytes but rather secreted via the bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is important to note that despite that SCN-DOX resulted in a high accumulation of DOX in the liver, better liver function than that in the animals received free DOX was observed at the end of the study, as demonstrated by a significant reduction of serum AST in mice treated with SCN-DOX (Figure 8). Of note, DOX is excreted predominantly through the hepatobiliary route [54] and there is a good negative correlation between serum AST activity and hepatic intrinsic clearance [55]. Therefore, it is tempting to speculate that SCN-DOX accumulated in the liver was not significantly taken up the hepatocytes but rather secreted via the bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…This might be related to the gen adverse effect on the liver. Gen is implicated in hepatocellular damage according to many studies (25). Liver is the organ where protein synthesis takes place, and when there is reduction in protein synthesis it is mostly related to liver illness, or to the excessive loss of protein in urine due to kidney disease (26).…”
Section: Discussionmentioning
confidence: 99%
“…The alteration in serum albumin is found more commonly in chronic liver disease. Therapeutic or prophylactic administration of an antioxidant leads to an increase in the level of albumin in the serum (Yokogawa et al, 2006)…”
Section: Effect Of Beets and Rosemary On Serum Bilirubin Total Protein Albumin Globulin And Albumin/globulin Ratio (A/g) Pattern Of Rats mentioning
confidence: 99%